PROYEKSI DATA MURID SMP MELALUI PENDEKATAN TEORI SISTEM MATEMATIKA DI PUSAT STATISTIK PENDIDIKAN, BALITBANG, DEPDIKNAS - Ikrar Pramudya (Widyariset, 2009)
This study discusses the application of the mathematical system theory in projection of data, especially educational data. This study is done by doing discussion of relevant theory and the appropriate mathematical system models. The result of the study is the existence of mathematical system model fitting in with requirement of projection of data and projection technique for n variable done simultaneously. Excess from projection of data with this approach is a consistent result of calculation and measurable error ofp rojection.